Depression, Diabetes, and Healthcare Utilization: Results from the Korean Longitudinal Study of Aging (KLoSA). - Hyun Kyung Lee; Seung Hee Lee (Tehran University of Medical Sciences, 2014)
The aim of this study was to explore the relationship between diabetes and depression and investigate the effects of comorbid diabetes and depression on healthcare utilization.The study sample included 10,179 Korean adults aged ≥ 45 years. The presence of diabetes was assessed by asking participants if the participants had ever been diagnosed with diabetes. Depression was measured using the 10-item Center for Epidemiological Studies-Depression scale. Healthcare utilization was assessed by self-report. Multiple logistic regression analyses were performed.Diabetes was positively associated with depression after controlling socioeconomic and health variables. Diabetic patients who had low socioeconomic status, who were obese, who were smokers, and who had higher numbers of chronic diseases had a higher depression risk. Diabetes and depression was associated with increased healthcare utilization. People with both diabetes and depression had significantly increased odds of multiple physician visits, multiple hospital admissions, and prolonged hospitalization compared with individuals with neither diabetes nor depression. Patients with both diabetes and depression had greater odds of multiple hospital admissions than patients with diabetes alone.We found a positive association between diabetes and depression. Depression in persons with diabetes is associated with increased multiple hospital admissions. More research is warranted to clarify an association between co-occurring depression with diabetes and increased healthcare utilization.